Integrin Requirement for Hippocampal Synaptic Plasticity and Spatial Memory - Chan, Chi-Shing (J Neurosci, 2003)
The establishment of memory requires coordinated signaling between presynaptic and postsynaptic terminals in the CNS. The integrins make up a large family of cell adhesion receptors that are known to mediate bidirectional signaling between cells or between cells and their external environment. We show here that many different integrins, including α3 and α5, are expressed broadly in the adult mouse brain and are associated with synapses. Mice with genetically reduced expression of α3 integrin fail to maintain long-term potentiation (LTP) generated in hippocampal CA1 neurons. Mice with reduced expression of the α3 and α5 integrins exhibit a defect in paired-pulse facilitation. Mice with reduced expression of α3, α5, and α8 are defective in hippocampal LTP and spatial memory in the water maze but have normal fear conditioning. These results demonstrate that several different integrins are involved in physiological plasticity and provide the first evidence of their requirement for behavioral plasticity in vertebrates.